PROSPECTIVE STUDY OF MATERNAL AND FETAL OUTCOMES IN WOMEN DIAGNOSED WITH THYROID DISORDERS IN FIRST TRIMESTER PREGNANCY. - Dr.B.Mounika; Dr.B.Nirmala Devi; Dr.L.Arundathi Devi (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background- During pregnancy, thyroid physiology undergoes considerable modifications prompting a re-evaluation of diagnostic thresholds and treatment protocols for thyroid. Due to the rising incidence of thyroid dysfunction during pregnancy, the present prospective study is critical in evaluating the maternal and fetal repercussions of thyroid disorders identified in the first trimester.Objectives - To assess the maternal and fetal outcomes in pregnancy with thyroid disorders.Materials and methods - The Present study involves screening of 200 eligible women diagnosed with thyroid disorders during first trimester. The patients are classified as euthyroid, hypothyroid and hyperthyroid based on their TSH levels.  They were treated and followed up till the completion of their pregnancy and delivery.Results - Among the 200 pregnant women with thyroid disorders, most of them N=138(69%) fall under age group of 21 to 30 years. Out of these N=191(95.5%) were hypothyroid and N=9 (0.5%) was hyperthyroid. In last trimester of pregnancy patients with TSH levels >3mIU/L associated with complications such as preterm birth N=5(2.5%), pre-eclampsia N=5(2.5%), Gestational diabetes mellitus N=3(1.5%), oligohydramnios N=5(2.5%), IUGR N=2(1%) and anemia , IUD and eclampsia with one case each i.e., N=1(0.5%).Conclusion - This study emphasizes that elevated TSH levels (>3mIU/L) is associated with increased risk of adverse outcomes like preterm birth, IUGR, Gestational diabetes mellitus and low birth weight. Thus early diagnosis, continuous monitoring and effective treatment is necessary during pregnancy to mitigate these risks and improve maternal and fetal outcomes.